Storozhenko М. S. Wear mechanisms of TiB2-SiC ceramic materials. - Стороженко, М.С. (Problems of Tribology, 2014)
This work is devoted to the investigation of TiB2-SiC ceramic materials wear behavior against steel counter body under dry sliding conditions. The TiB2-based ceramic materials with addition of 10%, 20%, 30% (wt.) silicon carbide were produced. The structure of TiB2-SiC materials consists of titanium diboride matrix and silicon carbide particles. It was determined that addition of 10-30 wt.% silicon carbide into titanium diboride results in the improvement of hardness and bending strength as compared with initial titanium diboride material. However, increase of SiC content up to 30wt.% leads to the growth of silicon carbide inclusion that decrease bending strength of TiB2-30wt.%SiC material comparing with TiB2-10wt.%SiC and TiB2-20wt.%SiC. The influence of TiB2-SiC ceramic materials structure on their wear behavior under dry sliding conditions was studied using block-on-ring tester at sliding speed of 0.5-15 m/s and constant load applied to the of 2 MPa. The worn surfaces were observed using optical and scanning electron microscopy to determine the wear mechanisms of TiB2-SiC ceramic materials against steel counterbody. It has been determined that high difference in hardness of mating surfaces causes the realization of abrasive wear mechanism in "ceramic material - steel" tribocouples at the sliding speed of 0.5 m/sec, that leads to the severe damages and high wear rate of steel counterbody (18 - 25 μm/km). At high sliding speeds (υ = 5 - 15 m/s) the intensive plastic deformation and transfer of steel counterbody material on the hard surface of TiB2-SiC ceramics promote the formation of Fe2O3, Fe3O4 oxide films on the contact surfaces. The oxide tribolayer further behaves as solid lubricant and prevents damages of mating surfaces. Such wear mechanism provides high wear-resistance of "ceramic material - steel" tribocouples (І = 1,6-2,5 μm/km) at high sliding speeds and load.